A responsabilidade tributária dos grupos econômicos: uma análise à luz da legislação vigente e da jurisprudência do STJ - Santos, Aline Bacelar Teixeira (2023)
The study aims to verify the existence of a valid normative foundation to regulate the liability of economic groups in the tax field. Initially, a constitutional matrix for tax liability is outlined, focusing on the principles of the supremacy of the Constitution, legality and legal certainty, as well as paying attention to the constitutional requirement that the supplementary law should regulate this matter. Subsequently, the legislative apparatus concerning tax liability of third parties is examined in order to verify whether it is sufficient to impose tax liability on legal entities that are members of the economic group. Next, a concept of economic group is established, and then we will analyze the legal provisions commonly used as a basis to try to hold the companies that make up the same economic group liable for taxes. After analyzing each of these legal hypotheses, the conclusion is that there is no valid regulation for this situation in the Brazilian tax system that meets the constitutional dictates, leaving it up to the Judiciary to decide the cases in which it will be possible to attribute tax liability to economic groups. Finally, the case law of the Superior Court of Justice on the subject is examined, emphasizing what the Court considers to be common interest for purposes of tax liability and the divergence currently existing to the possibility of instauration of the Incident of Disregard of Legal Entity in tax enforcement actions